Students’voice in English course development at the university. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2008)
In a climate of higher education which is increasingly client-based, student needs and preferences are given more attention, and the sphere of student influence extends from recreational and infrastructural facilities to teaching and learning practices and administration. In teaching and learning, traditionally the repositioning of courses is a top-down directive but bottom-up feedback from lecturers is also instrumental in course development. In the course evaluation, the lecturers may not only take account of the requirements of the discipline and the profession but are compelled to consider student preferences.